A Fauna de Morcegos Fósseis como Ferramenta na Caracterização de Paleoambientes Quaternários. - Leonardo Santos Avilla; Gisele Regina Winck; Vanessa Maria Rodrigues Francisco; Bruno Bret Gil; Alexandre Granhen; Débora Gabriel Costa (Anuário do Instituto de Geociências, 2007)
This study proposes to reconstruct the paleoenvironment from Quaternary sites of the caves in the sertão baiano and Lagoa Santa region during the Pleistocene. The paleofauna of bats from these sites were compared to the extant fauna of 25 localities, representing most important Neotropical biome. This study was possible because all bat fossil species from both sites were elements of the extant Neotropical fauna, excepting Desmodus draculae. Because bats are considered goodenvironmental definers, the association of extant and fossil fauna permits the recognition of similar environments. The similarity between faunas was analyzed by Jaccard index with a posterior grouping analysis by UPGMA. The paleofauna of Lagoa Santa matched to Caatinga fauna, suggesting a dry and open environment adjacent to the Lagoa Santa cavesduring the Pleistocene. The paleofauna of sertão baiano caves matched to neither of the analyzed faunas. Most authorssuggest that fossil record of the sertão baiano caves represents a faunal mixture. The dissimilarity between the paleofaunaof bats from the sertão baiano caves and the other analyzed faunas resulted of this study is in agreement to the argumentof a faunal mixture represented by the former.